Evaluating an intervention for family members of people who use drugs in Vietnam. (September 2020) - Li, Li; Lin, Chunqing; Liang, Li-Jung; Feng, Nan; Pham, Loc; Hien, Nguyen Tran
Highlights: This study evaluates an intervention targeting family members of drug users. Greater improvement in family functioning was observed in the intervention group. Community intervention has the potential to benefit families impacted by drug use. The special needs of family members should be considered in future intervention design.